The Incidence Of Intestinal Parasites Among Children In Hivi Pediatric Hospital, Duhok, Iraq - Hussein, Jehan N.; Meerkhan, Azad A. (Science Journal of University of Zakho, 2019)
This study has conducted in Hivi Pediatric Hospital, Duhok Province, Iraq, to estimate the gastrointestinal parasites infection among patients contacted this hospital. Overall patients, 22.27% (261/1,172) were diagnosed as infected by parasites; more of them were from summer season with the infection rate of 24.83% (216/870) versus 14.90% (45/302) in autumn, rural residence had a greater rate of infection 65.90% (172/261) as compared with urban residence 34.09 (89/261), males were more infected than females (63.98% versus 36.02% respectively), the age group of three years and less had the highest rate of infection, while the age group of more than 9 years had the lowest rate (57.85%, 4.98% respectively). Concerning the children feeding way, the artificially feeding had the highest rate then mixed feeding and Breastfeeding (58.16%, 25.53% and 16.31% respectively). As general, the infection with protozoa (84.67) was higher than helminthes (18.01%) with some cases of infection by both of protozoa and helminthes (4.98). Regarding each parasite separately, Entamoeba histolytica had the highest infection rate then Giardia lamblia., Enterobius vermicularis, Cryptosporidium Spp., Entamoeba coliandBlastocystis hominis (38.70%, 25.67%, 18.01, 9.20%, 6.51 and 4.60 respectively).
Keywords: Children Infection; Protozoa; Helminthes; Parasitic Infection; Gastrointestinal Infection